Cutting-edge Issues in Business Ethics Continental Challenges to Tradition and Practice - Painter-Morland, Mollie; Werhane, Patricia (Issues in Business Ethics, 2008)
This volume is one of the very few publications dedicated to the challenges that Continental philosophy poses to the field of Business Ethics. The authors want to draw attention to the work of Continental philosophers who have been relegated to the fringes of Business Ethics scholarship, and present some critical perspectives that have been ignored within Business Ethics practice. As such, this volume provides a critique of many of the assumptions that underpin traditional approaches to Business Ethics, and urges its readership to rethink moral agency and epistemology, as well as Business Ethics pedagogy.